The locus of knowledge externalities and the cost of knowledge. Issue 8 (3rd August 2017) - Antonelli, Cristiano; Colombelli, Alessandra
ABSTRACT: The locus of knowledge externalities and the cost of knowledge. Regional Studies . This paper provides an extended Crépon–Duguet–Mairesse (CDM) approach to analyse jointly the simultaneous effects of knowledge spillovers in the knowledge-generation and technology production functions. It introduces the distinction between imitation and knowledge externalities and articulates the hypothesis that spillovers yield their effects via three well-distinct mechanisms: (1) knowledge externalities that exert positive and direct effects on the knowledge-production function and (2) indirect effects on the technology-production function via their effects on the cost of knowledge; and (3) imitation externalities that exert direct and positive effects on productivity in the technology-production function. We test our hypotheses on a large panel of Italian companies distributed in NUTS-2 regions for the period 2005–09. The econometric analysis consists of a model comprising a system of equations that test the simultaneous role of spillovers in the knowledge-generation and technology-production functions with the inclusion of endogenous knowledge costs. The results confirm that the access to external knowledge – as an input in the knowledge-generation function – plays a key role in increasing the knowledge output and – as an input in the technology-production function – has positive indirect and direct effects on the productivity of firms.